Oxygen-deficient WO3−x@TiO2−x core–shell nanosheets for efficient photoelectrochemical oxidation of neutral water solutions. Issue 28 (3rd July 2017) - Yuan, Kaiping; Cao, Qi; Lu, Hong-Liang; Zhong, Miao; Zheng, Xiuzhen; Chen, Hong-Yan; Wang, Tao; Delaunay, Jean-Jacques; Luo, Wei; Zhang, Liwu; Wang, Yuan-Yuan; Deng, Yonghui; et al.
Abstract : Precisely controlled WO3– x @TiO2– x nanosheet photoanodes are fabricated for efficient and stable PEC water oxidation. Abstract : Preparation of highly active, stable and earth-abundant photoanodes for water oxidation is an important strategy to meet the demand of developing clean-energy technologies. In this paper, efficient and stable photoanodes based on oxygen-deficient black WO3− x @TiO2− x core–shell nanosheets with precisely controlled shell thickness have been fabricated for photoelectrochemical (PEC) conversion from neutral water solutions. The black WO3− x @TiO2− x core–shell nanosheet photoanode with the shell thickness of ∼15 nm achieved around 8 times higher photocurrent density (∼3.20 mA cm −2 ) than the pure WO3 photoanode at 1.23 V vs. the RHE. An improved onset potential with long-term PEC durability was also realized with the obtained black WO3− x @TiO2− x core–shell nanosheet photoanodes. The promoted PEC water oxidation performance was likely to be originated from enhanced light absorption, interfacial charge transfer and charge separation in these WO3− x @TiO2− x nanosheets which were revealed by finite-difference time-domain simulations and specific band alignment, along with optical and electrochemical spectroscopic evidence. In a word, such black WO3− x @TiO2− x nanosheet photoanodes suggest many exciting opportunities for PEC water splitting toward highly efficient solar fuel generation and many other PEC sensing applications.